Informal Credit Markets, Common-pool Resources and Education - Marie-Catherine Riekhof; Frederik Noack (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
The paper analyses the effect of interest rate changes on education and child labor in an economy with a high-skilled sector, a low-skilled sector and fragmented credit markets. The high-skilled sector takes educated labor as input. The low-skilled sector takes unskilled labor, physical capital and natural common-pool resources as inputs. Credit supply consists of (a) loans with collateral in form of productive investments in the low-skilled sector and (b) higher-priced loans without collateral. Lower interest rates increase the net present value of the returns to education. They also reduce costs of capital investment in current production. This increases labor productivity and the opportunity costs of education. Overuse of the common-pool resource can reverse this productivity effect. We show that the overall effect of interest rate changes on education depends on the initial wealth of the household, resource use and the credit market segment that is subject to improvements.
Keywords: D13; D91; J24; O16; Q20; 330; Informal Credit Markets; Education; Common-pool Resources; Child Labor; Fragmented Credit Markets; Common-pool Externality; Kreditmarkt; Informelle Wirtschaft; Humankapital; Bildungsinvestition; Kinderarbeit; Externer Effekt; Theorie